Law Enforcement Updates on Human Trafficking Crimes Through Monitoring of Social Media-Based Digital Recruitment and Online Platforms by the Indonesian Police - Zikri Muamar; Syafruddin Syafruddin; Kif Aminanto (Journal Customary Law, 2026)
The development of digital technology has shifted the pattern of human trafficking crimes from conventional methods to anonymous, rapid, and cross-border recruitment based on social media and online platforms. This study aims to analyze the weaknesses of the Indonesian legal system in addressing digital recruitment in human trafficking crimes, examine the problems of law enforcement by the Indonesian National Police, and formulate an ideal legal reconstruction and reform in dealing with digital-based human trafficking. This study employs a normative juridical method that combines legislative and conceptual approaches by analyzing various regulations related to human trafficking crimes, information technology, cyber law enforcement, and legal protection. The results of the study indicate that national regulations, such as Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking and the Law on Information and Electronic Transactions, do not specifically regulate the supervision of digital recruitment, digital platform accountability, cyber patrols, digital surveillance, and cross-border enforcement mechanisms. In addition, the Indonesian National Police still faces limitations in cyber policing, minimal digital forensic capacity, difficulties in tracking anonymous accounts, and weak inter-agency coordination in handling digital-based human trafficking. Therefore, legal reconstruction and reform are needed through strengthening cyber policing, integrating cyber patrols and digital intelligence, optimizing electronic evidence, regulating digital platform obligations, and strengthening international cooperation to build a law enforcement system that is responsive, preventative, and adaptive to developments in digital technology.